OX40 expression in hepatocellular carcinoma is associated with a distinct immune microenvironment, specific mutation signature, and poor prognosis. (3rd April 2018) - Xie, Kunlin; Xu, Lin; Wu, Hao; Liao, Haotian; Luo, Lin; Liao, Mingheng; Gong, Jianping; Deng, Yang; Yuan, Kefei; Wu, Hong; Zeng, Yong
ABSTRACT: Immunotherapy's effect against hepatocellular carcinoma (HCC) is hampered by immunosuppressive mechanisms in the tumor microenvironment. We assessed the clinicopathologic and biologic relevance of OX40, a costimulatory molecular expressed by regulatory T cells (Tregs), in HCC. We analyzed the immunohistochemistry data of 316 patients treated at West China Hospital (WCH) and the RNA sequencing data of 370 patients in The Cancer Genome Atlas (TCGA) to determine the clinicopathologic significance of OX40 in HCC. We also assessed associations between OX40 and multiple immune-related markers. Using the TCGA data, we further characterized the transcriptome, immune cell functions, and mutation signature related to OX40. We found that OX40 expression was higher in HCC than in adjacent liver tissue. In the WCH set, 136 (43%) patients had high-OX40 expression, whereas in the TCGA set, 247 (67%) patients had high-OX40 expression as determined by the X-tile program. High-OX40 expression was associated with high serum alpha-fetoprotein level, vascular invasion, and shorter survival. The prognostic significance of OX40 was validated in additional cohorts. OX40 expression was also associated with CD8A, CD68, LAG3, TIM-3, and PD-1 expression. High-OX40 expression tumors were characterized by upregulated cytokines and exhaustion-specific markers. Analysis of the enrichment data of immune cell types indicated that OX40 expression was associated with the functions of macrophages, plasmacytoid dendritic cells, and co-inhibitory T cells. Finally, high-and low-OX40 expressions were associated with mutations in AKT/mTOR and Wnt/β-catenin signaling, respectively. These results indicate that high-OX40 expression represents the activation of multiple immunosuppressive pathways and provide a rationale for the therapeutic targeting OX40 in HCC patients.